Nationalism of Border Society: Case Study of Sangir People, Sangihe Regency - Pamungkas, Cahyo (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2016)
This study aims to describe how maintenance of nationalism has been conducted by the state toward border communities and how far citizens understand the concept of the Homeland and border, national pride, and apprehending the meaning of nationalism. The main source of data used in this study was the result of interviews, focus group discussions, participant observation, and literature studies conducted in Tahu, and Marore (Sangihe). The findings in this study are as follows. First, the acquisition of knowledge about the Homeland as a political concept, as well as national pride border communities today is increasing due to the development of information technology development and maintenance of nationalism efforts undertaken by the Government. Second, nationalism is defined by the state as measured by peopleâs understanding toward the concept of nationalism which is less relevant to the socio-economic context of low income border communities. Third, the maintenance of nationalism efforts can be done to accommodate and provide space for cultural identity development of border communities in Indonesia.